Protestant missionaries in Spain, 1869-1936 : shall the papists prevail? - Eaton, Kent, 1968- (Lexington Books, 2015)
This book examines the history of the Protestant denominations in Europe that attempted to bring their churches to Spain just prior to the creation of Spain's First Republic (1873-74), when religious liberty briefly existed.